Cognitive therapy for depression : the moderating effect of personality beliefs on homework adherence and outcome for depression : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Auckland, New Zealand - Prosser, Janis Ann (Massey University, 2012)
Cognitive Therapy (CT) is an efficacious treatment for Major Depressive Disorder (MDD) (Butler, Chapman, Forman, & Beck, 2006). Homework (HW) tasks are an integral facet of this therapeutic modality (Beck & Tompkins, 2007), and are believed to be one of the active ingredients in its therapeutic effect (Rees, McEvoy, & Nathan, 2005). The current literature indicates that not all clients adhere to their HW assignments equally, with some evidence to suggest that this may be attributable to problem type (Kazantzis, Deane, & Ronan 2000). MDD is highly comorbid with personality disorders (PD) (George, Milklowitz, Richards, Simoneau & Taylor, 2003) and the beliefs that underpin these syndromes, as conceptualised in cognitive theory, have been anecdotally linked to the variance in HW adherence (Kuyken, Kurzer, DeRubeis, Beck & Brown, 2001). This current research is the first to investigate the moderating role personality beliefs have on HW adherence and outcome in CT for depression. This current study was situated within a larger collaborative research project investigating HW in the treatment of depression, conducted at the School of Psychology, Massey University, Albany, and in partnership with Harvard University and the London Institute of Psychiatry. A final sample of 27 participants experiencing their index episode of MDD were recruited from the wider Auckland region. Participants attended up to 20-‐sessions of CT for depression, and follow-‐up sessions at 2-‐ and 6-‐months, provided by doctoral students. Depression severity was measured at baseline and every session with the Beck Depression Inventory – Second Edition (BDI-‐II). Personality beliefs were assessed at Session 8 with the Personality Beliefs Questionnaire – Short Form (PBQ-‐SF). Homework adherence was assessed from Session 2 with the Homework Rating Scale – Second Edition (HRS-‐II). A prospective longitudinal multi-‐level modelling design was utilised and data were analysed on the SPSS suite. All participants experienced symptom reduction across treatment duration with a mean percentage improvement of 68.1%. A total of 13 (49%) participants endorsed at least one scale of the PBQ-‐SF and 51% (n=14) did not. Results indicated that the endorsement of personality beliefs resulted in higher levels of depressive severity at intake, and moderated client rated HW adherence and the beliefs factor of the HRS-‐II. Specifically, personality beliefs were related to less adherence with HW tasks and higher residual symptoms of depression at termination. Therapist rated HW had no effect on outcome. The limitations, contributions to the literature and implications for clinical practice are discussed.
Keywords: Cognitive therapy; Depression